THE EFFECT OF SERVICE QUALITY AND RELATIONSHIP MARKETING ON CUSTOMER SATISFACTION AND THEIR IMPACT ON CUSTOMER LOYALTY AT MAYO DIET MEDAN CATERING - Laily Artha Nasution; Paham Ginting; Arlina Nurbaity Lubis (RADJA PUBLIKA, 2025)
Globalization brings changes to human lifestyles from bad to better, from not prioritizing health to making health a priority in one's life. Health can be obtained in several ways, one of which is maintaining food intake to avoid consuming food carelessly in the sense of fatty and containing high cholesterol. Mayo Diet Medan provides health food products by not consuming rice and salt for a specified time, in order to control electrolyte and water levels in the body to facilitate the destruction of bad fats and processing fat into energy for daily activities. Mayo Diet Medan is one of the health food catering located in the city of Medan. The purpose of this study was to determine the effect of physical evidence, reliability, responsiveness, assurance, empathy and relationship marketing on customer satisfaction and its impact on customer loyalty Mayo Diet Medan. This type of research is Descriptive Quantitative. This study used the Proposive sampling method to collect data from 86 respondents with a sample using the Slovin formula. The data analysis method used was path analysis using SPSS software. The results of the study show that sub-model I shows that service quality consisting of reliability, responsiveness, assurance has a positive and significant influence on Customer Satisfaction. Service quality in the form of empathy has a positive but insignificant influence on customer satisfaction, and for the physical evidence variable has a negative but insignificant influence on customer satisfaction at Mayo Diet Medan. Relationship Marketing has a positive and significant influence on Customer Satisfaction at Mayo Diet Medan. From the results of the study conducted in sub-model II shows that the service quality variable consisting of physical evidence, reliability, assurance and empathy has a positive and significant influence on loyalty. The service quality variable in the form of responsiveness has a negative but insignificant influence on customer loyalty. Relationship marketing has a positive and significant influence on customer loyalty. And customer satisfaction has a positive and significant influence on customer loyalty. From the results of the study conducted shows that service quality consisting of reliability, responsiveness, assurance, empathy has a positive influence on customer loyalty through Customer Satisfaction at Mayo Diet Medan. Physical evidence has a negative influence on customer loyalty through customer satisfaction because Mayo Diet Medan has provided the best raw materials and has its own operational standards regarding employee appearance and neatness.